Double-exponential refractive index sensitivity of metal-semiconductor core-shell nanoparticles: the effects of dual-plasmon resonances and red-shift - Zhang, Hailong; Cao, Pengfei (RSC Advances, 2018)
In order to improve the refractive index sensitivity of a localized surface plasmon resonance (LSPR) sensor, we present a new type of LSPR sensor whose refractive index sensitivity can be improved by greatly increasing the plasmon wavelength red-shift of metal-semiconductor core-shell nanoparticles (CSNs). Using extended Mie theory and AuCu2−xS CSNs, we theoretically investigate the optical properties of metal-semiconductor CSNs in the entire near-infrared band. Compared with dielectric-metal and metal-metal CSNs under the same conditions, the metal-semiconductor CSNs have a higher double-exponential sensitivity curve because their core and shell respectively support two LSPRs that greatly increase the LSPR red-shift to the entire near-infrared range. It is worth noting that the sensitivity can be improved effectively by increasing the ratio of the shell-thickness to core-radius, instead of decreasing it in the case of the dielectric-metal CSNs. The underlying reason for the enhancement of sensitivity is the increase of repulsive force with the enlargement of shell thickness, which is different from the dielectric-metal CSNs. This design method not only paves the way for utilizing metal-semiconductor CSNs in biology and chemistry, but also proposes new ideas for the design of sensors with high sensitivity.
Gesehen am 31.03.2020